Statistik di Perpustakaan Umum Gunung Bungsu Kabupaten Tanah Datar Tahun 2013-2015 - Afdhal, Afdhal; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about statistics in general Public Library of Gunung Bungsu Tanah Datar Â 2013-2015 as a means of comparison information and materials in the Public Library of Gunung Bungsu Tanah Datar. This paper also aims to describe the statistics in the Public Library of Gunung Bungsu as a means of information and comparison at the Public Library of Gunung Bungsu Tanah Datar. The process of data collection is done with the study of documents by collecting data directly from the original source, that is by doing interviews and observations in the Public Library of Gunung Bungsu Tanah Datar. Based on the discussion can be concluded : 1) a general overview statistic in the Public Library of Gunung Bungsu Tanah Datar Â 2013-2015 as follows: Public Library of Gunung Bungsu Tanah Datar, Vision and Mission, Objectives, Personnel in Public Library of Gunung Bungsu Tanah Datar room, Public Library of Gunung Bungsu Services Public Library Gunung Bungsu, Membership, Infrastructures, Systems Service Reference Collection at the public library Gunung Bungsu Tanah Datar, Storage Reference Collection in the Public Library of Gunung Bungsu, Procedures Loan and Refund Reference Collection at the Public Library Gunung Bungsu Tanah Datar, Problems Facing Public Library Service at Gunung Bungsu Tanah Datar; 2) Library general statistic of Gunung Bungsu Tanah Datar Year 2013-2015 as follows: Statistical Library Materials in Public Library of Gunung Bungsu Tanah Datar Year 2013-2015, Statistics Lending Library Printed Materials in Public Library of Gunung Bungsu Year 2013-2015, Visitor Statistics in the Public Library of Gunung Bungsu Tanah Datar 2013-2015.Keywords: Statistics, Public Library, Gunung Bungsu, Tanah Datar